2018
DOI: 10.1123/pes.2017-0127
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, BMI, and Blood Pressure in US Youth: NHANES 2003–2006

Abstract: This study showed a significant independent and combined association of BMI and physical activity with blood pressure in youth. Interventions need to focus on the reduction of fatness/BMI as a way to reduce the cardiovascular risk in youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
1
9
0
2
Order By: Relevance
“…BFP is the percentage of fat content in total body weight, which can reflect the degree of obesity in the body. Some studies have found that higher level of PA was related to lower probability of obesity and smaller BFP [32,33] .The team members in our study conducted field surveys of residential areas studied, and there was almost no traffic jam and the no driver exceed the speed limit. However, we found that the number of fast food restaurants, specialty restaurants and snack bars in the survey area was more than other residential areas.…”
Section: Discussionmentioning
confidence: 81%
“…BFP is the percentage of fat content in total body weight, which can reflect the degree of obesity in the body. Some studies have found that higher level of PA was related to lower probability of obesity and smaller BFP [32,33] .The team members in our study conducted field surveys of residential areas studied, and there was almost no traffic jam and the no driver exceed the speed limit. However, we found that the number of fast food restaurants, specialty restaurants and snack bars in the survey area was more than other residential areas.…”
Section: Discussionmentioning
confidence: 81%
“…Obesity is characterized by a high BMI value (more than 25 kg/ m2). Previous studies have shown that reducing BMI can significantly reduce the incidence of hypertension and cardiovascular disease (Betz et al, 2018;Zhou et al, 2018;Vrettos et al, 2020). Our study data show the same thing, where BMI has a correlation with systolic blood pressure.…”
Section: Correlative Analysismentioning
confidence: 99%
“…Besides the accuracy and choice of methods for PA measurement, the inconsistency in Results may also be due to the initial health status of children in various studies, which may greatly affect the observed associations [16,20]. For instance, factors known to affect blood pressure among children are age, gender, BMI, race/ethnicity and socioeconomic status [38][39][40][41]. Therefore, in the present study, we corrected for age, gender and BMI z-score in the linear regression model.…”
Section: Plos Onementioning
confidence: 99%